2019
DOI: 10.1155/2019/4798906
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping of Echinococcus Species from Livestock in Kajiado County, Kenya

Abstract: Cystic Echinococcosis (CE) is a widespread neglected zoonotic disease and is caused by the larval stage of the dog tapeworm Echinococcus granulosus sensu lato. CE is more frequent in livestock-rearing areas and where people live a nomadic or seminomadic lifestyle such as in Kajiado County, Kenya. There is limited data on CE disease situation in the county of Maasailand; the present study, therefore, reports on the prevalence of CE in cattle, sheep, and goats and their relative importance in CE transmission in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…and its metacestode stage, hydatid cyst (Menekşe et al ., 2012). Echinococcus granulosus is cosmopolitan in distribution, but concentrated in the major livestock keeping or rearing areas, especially of South America, the Mediterranean, East Africa, Russia, Central Asia, China and Australia (Grosso et al ., 2012; Fallahizadeh et al ., 2019; Nungari et al ., 2019; Ramos-Sarmiento & Chiluisa-Utreras, 2020). In Saudi Arabia (KSA), several studies have indicated that hydatid disease is endemic where dogs are one of the major factors that distribute the disease, as well as the direct sources of human infection represented in home slaughtering of camel and sheep (Abu-Eshy, 1998; Al-Mofleh et al ., 2000; Adewunmi & Basilingappa, 2004; Rashed et al ., 2004; Al-Malki & Degheidy, 2013; Toulah et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…and its metacestode stage, hydatid cyst (Menekşe et al ., 2012). Echinococcus granulosus is cosmopolitan in distribution, but concentrated in the major livestock keeping or rearing areas, especially of South America, the Mediterranean, East Africa, Russia, Central Asia, China and Australia (Grosso et al ., 2012; Fallahizadeh et al ., 2019; Nungari et al ., 2019; Ramos-Sarmiento & Chiluisa-Utreras, 2020). In Saudi Arabia (KSA), several studies have indicated that hydatid disease is endemic where dogs are one of the major factors that distribute the disease, as well as the direct sources of human infection represented in home slaughtering of camel and sheep (Abu-Eshy, 1998; Al-Mofleh et al ., 2000; Adewunmi & Basilingappa, 2004; Rashed et al ., 2004; Al-Malki & Degheidy, 2013; Toulah et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most notable difference between this study and those of high-prevalence regions is the rare occurrence of E. granulosus s.s. Although previous studies in Kenya have confirmed sheep as the main intermediate host of E. granulosus s.s. where cysts attained high fertility rates (Dinkel et al, 2004;Addy et al, 2012;Nungari et al, 2019), in this study, no cyst from sheep presented this species. The analysis of more cysts from sheep in this region is required.…”
Section: Discussionmentioning
confidence: 49%
“…The majority of the cysts in this study were isolated from the liver, which is common since the liver is the first organ encountered by the migrating oncosphere after leaving the intestines. This finding agrees with observations in Maasailand, Kenya (Addy et al ., 2012; Odongo et al ., 2018; Nungari et al ., 2019) and in Sudan (Elmahdi et al ., 2004). These results, however, differed with reports from other regions in Kenya that found the lung as the most parasitized organ (Njoroge et al ., 2002; Kere et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations